(untitled) (Economics and region, 2022)
The article reveals the peculiarities of financial support of amalgamated hromadas, the main factors of structural influence on the formation of the revenue part of the budget of the hromadas. A comparative description of the financing of the Kalytvenska and Myronivska hromadas has been carried out. The priority ways of increasing the financing of the ATC are revealed. In accordance with the statistics, the budget of the Kalytvenska hromada received income in the amount of UAH 83,722.1 thousand, of which inter-budgetary transfers – UAH 40,490.9 thousand. The share of revenues in the context of the main types of taxes is formed by: tax and fee on personal income; single tax; land payment; excise tax; real estate tax; other taxes and fees. The scientific article notes that the main areas of expenditure of the Myronivska community in 2020 were education and healthcare. This is due to the envisaged subventions for educational and medical institutions. It is noted that ensuring the full formation of own revenues of local budgets in the amounts that contribute to improving the efficiency of socio-economic development of administrative-territorial units should be carried out by changing the standards for the share of own revenues of local budgets (i.e., excluding transfers) in the consolidated budget at the level of not less than 30% due to the redistribution of additional sources of its formation in favor of local budgets; monetary valuation (revaluation) of land in settlements and outside them, taking into account the market factor; development of a program of work with the public to explain the benefits of the introduction of real estate tax and the mechanism of formation and collection of this tax using the media (radio, television, mass distribution of printed materials); regulatory regulation of additional revenues to local budgets by expanding their own sources, in particular, tax or tariff incentives for rational attitude to the sorting and disposal of household waste, the introduction of fees for advertising in cultural and historical centers.